Distributed cognition and “Course of action” - Jacques Theureau (Activités)
The ‘distributed cognition’ research program, initiated by Edwin Hutchins, has contributed to the development of the ‘course of action’ research program from 1987 to the present day. Edwin Hutchins having recently recognized the close relationship between his latest research, developed in terms of embodied and distributed cognition, and that on the enaction paradigm, of which this ‘course of action’ research program is a part, the question now arises of the definition of an “augmented ‘course of action’ research program”. In relation to this enaction paradigm, such a program should go into greater depth and provide a new synthesis of the ‘distributed cognition’ research program’s past contributions to the ‘course of action’ research program and integrate its new contributions. This in-depth analysis, synthesis and renewal of the contributions to the ‘course of action’ research program are facilitated by the mutual contribution and addition of different theoretical and methodological results obtained by the two research programs over recent decades. In this paper we will present our personal view of the answer to this question.